INVESTIGAÇÃO DA OCORRÊNCIA DO FENÓTIPO LACTASE PERSISTENTE E DE SOBREPESO EM PRATICANTES DE ATIVIDADE FÍSICA Dissertação - BONILHA, CAIO SANTOS (2015)
Lactose intolerance is a condition related to distinct clinical symptoms that accompany lactose maldigestion. The prevalence of this intolerance is estimated at 75% of the global population. This adverse reaction to food is a public health problem and is associated with a significant negative impact on quality of life. Genotyping through LCT-12910C>T polymorphism detection method and subsequent identification of the lactase persistent phenotype has been widely used for diagnostic purposes. To provide a better understanding of the pathophysiology of this disease, it is important to develop new studies evaluating the impact of nutritional parameters, such as overweight, in the occurrence of this phenotype. The presence of overweight has grown quickly in recent decades. Even in groups of physically active individuals these rates are high. In this context, it is important to use different anthropometric measurements in the estimation of nutritional status. Methods of skinfold thickness, body mass index, waist circumference and waist-to-height were chosen for classification purposes of nutritional status and the presence of other disorders. We recruited 22 practitioners of physical activities at the school of pharmacy of the Midwest State University, in order to assess the occurrence of lactase persistent phenotype and overweight through anthropometric measures. The detection of the polymorphism was performed by Polymerase Chain Reaction, with subsequent sequencing in external laboratory and analysis with sequential alignment software. Half of the patients were overweight, while the other half had a body mass index in the normal range. Eight were classified as primary intolerant, through the presence of the phenotypic trait lactase non-persistent. Ten subjects had persistent lactase phenotype. It was not possible to perform sequencing on four samples. This study suggests that the occurrence of lactase persistent phenotype is increased in practice physical activities with body mass index in the normal than in physically active overweight individuals range.